Do we underestimate maximal oxygen uptake in cancer survivors?: findings from a supramaximal verification test - Schneider, Justine; Schlüter, Kathrin; Wiskemann, Joachim; Rosenberger, Friederike (Applied physiology, nutrition, and metabolism, 2020)
Cancer survivors demonstrate a reduced maximal oxygen uptake, which is clinically relevant in terms of overall survival. However, it remains uncertain whether they attain their “true maximal oxygen uptake” in a cardiopulmonary exercise test (CPET). In the present study, a supramaximal verification bout (Verif) was applied in cancer survivors to confirm attainment of maximal oxygen uptake. Seventy-five participants (age, 61 ± 12 years; n = 43 females with breast cancer and n = 32 males with prostate cancer, 6-52 weeks after primary therapy) performed a CPET on a cycle ergometer and a Verif at 110% peak power output. As verification criterion, maximal oxygen uptake in Verif should not exceed maximal oxygen uptake in CPET by >3%. On average, maximal oxygen uptake was significantly lower in Verif compared with CPET (1.60 ± 0.38 L·min-1 vs. 1.65 ± 0.36 L·min-1, p = .023). On the individual level, n = 51 (68%) satisfied the verification criterion, whereas n = 24 (32%) demonstrated a higher maximal oxygen uptake in Verif. n = 69 (92%) fulfilled ≥2 secondary criteria for maximal exhaustion in the CPET. While maximal oxygen uptake was not underestimated in the CPET on average, one-third of cancer survivors did not attain their true maximal oxygen uptake. Verif appears feasible and beneficial to confirm true maximal oxygen uptake in this population. Furthermore, it might be more reliable than secondary criteria for maximal exhaustion. Novelty In about one-third of cancer survivors, maximal oxygen uptake is underestimated by a CPET. This underestimation of maximal oxygen uptake is not necessarily indicated by secondary criteria for maximal exhaustion. A supramaximal verification bout appears feasible and helpful for the determination of maximal oxygen uptake in cancer survivors.